1975
DOI: 10.1017/s0047404500006680
|View full text |Cite
|
Sign up to set email alerts
|

The question of tag questions in women's speech: they don't really use more of them, do they?↓

Abstract: The authors investigate Robin Lakoff's dual claim that women use tag questions in more conversational situations than do men and that such questions signify an avoidance of commitment, causing the speaker 'to give the impression of not being really sure of himself, of looking to the addressee for confirmation, even of having no views of his own'. They find that in an at least one genuine social context, men did, and women did not, use tag questions, both formal and informal, so the claim is open to serious dou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
84
1
2

Year Published

1985
1985
2016
2016

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(88 citation statements)
references
References 2 publications
1
84
1
2
Order By: Relevance
“…In empirical investigations, Fishman (1980) and Eakins and Eakins (1978) found that women used tag questions more often than men. Other researchers, however, have found that tag questions were used more by men than by women (e.g., Dubois and Crouch, 1975;Lapadat and Seesahai, 1977).…”
Section: Conversational Division Of Labormentioning
confidence: 98%
“…In empirical investigations, Fishman (1980) and Eakins and Eakins (1978) found that women used tag questions more often than men. Other researchers, however, have found that tag questions were used more by men than by women (e.g., Dubois and Crouch, 1975;Lapadat and Seesahai, 1977).…”
Section: Conversational Division Of Labormentioning
confidence: 98%
“…)-that can be inserted into a wide variety of sentences. A number of studies have reported that females use more often tag questions (e.g., McMillan, Clifton, McGrath, & Gale 1977;Mulac & Lundell 1986) although others have found the opposite (e.g., Dubois & Crouch 1975). Besides this, gender differences have also been examined by studying the actual words people use.…”
Section: Rationale and Criteria For Designing The Questionnaire For Tmentioning
confidence: 99%
“…Dubois & Crouch, 1975;Cameron et al, 1989;and Brower et al, 1979) who do not necessarily confirm those findings. However, as Wardhaugh (2006, p. 321) says, some "investigators did find, however, that the gender of the addressee was an important variable in determining how a speaker phrased a particular question".…”
Section: Introductionmentioning
confidence: 96%